Is corporate real estate at a crossroads?. Issue 4 (4th November 2014) - Harris, Rob; Cooke, Howard
Abstract : Purpose: – The purpose of this article is to provide an overview of the way that corporate real estate (CRE) has developed in the UK since the early 1990s. Design/methodology/approach: – Review of how various professional bodies, occupiers and landlords have responded to the changing business and workplace environment. Findings: – CRE managers and the professional bodies that represent them are at a crossroads. Whilst the business world has evolved since 1990, the CRE sector has not and faces the prospect becoming purely a technical rather than a strategic subject. Originality/value: – A review of what has happened and not new research.